Effect of Discontinuous Yielding on the Strain Hardening Behavior of Fine-Grained Twinning-Induced Plasticity Steel - Kang, Singon; Jeong, Sujin; Ahn, Yeon-Sang (Frontiers in Materials, 2021)
The yielding of a high Mn twinning-induced plasticity steel was examined in three fine-grained specimens recrystallized at 700 ºC for 5 min with different cooling conditions. While the stress-strain curves of furnace-cooled and air-cooled specimens exhibit a stress drop, the drop was not observed in the water-quenched specimen. Meanwhile, a simple analysis of the displacement data confirms the occurrence of localized deformation at the beginning of the plastic deformation in the three tensile specimens with different cooling conditions. This localized deformation corresponds to the Lüders strain during discontinuous yielding. The degree of valley-type strain hardening rate evolution at an early stage of the tensile deformation is dependent on the discontinuity of the yielding rather than the deformation twinning kinetics.